ІНСТИТУЦІЙНІ ПЕРЕДУМОВИ ВПРОВАДЖЕННЯ БЕЗПЕКООРІЄНТОВАНОГО УПРАВЛІННЯ В УМОВАХ СУЧАСНИХ ВИКЛИКІВ СФЕРИ ОХОРОНИ ЗДОРОВ’Я - Валерій ГАРБУЗЮК (Development Service Industry Management, 2026)
The article examines the institutional prerequisites for implementing security-oriented management in the healthcare sector under contemporary global and national challenges. It is substantiated that the transformation of the healthcare system is taking place under the influence of a complex set of interrelated factors, including workforce shortages and professional burnout among healthcare workers, the increasing severity of patients’ conditions, changes in financing models, transformation of the regulatory environment, the growing role of the patient as a consumer, digitalization, and the development of artificial intelligence and biomedical innovations. The impact of population ageing, the spread of chronic and non-communicable diseases, the COVID-19 pandemic, military conflicts, financial instability, and cyber threats on the functional capacity and resilience of healthcare institutions is revealed. Global exogenous and national endogenous transformation factors that determine institutional frameworks, resource provision, human resource policies, financial decisions, and organizational models of healthcare institutions are systematized. The dynamics of key indicators of the development of the global healthcare system are analysed, including life expectancy, per capita healthcare expenditure, and the availability of healthcare workers and hospital beds. It is established that contemporary crises are not temporary deviations but rather form a new permanent reality in which healthcare system resilience should be viewed as its ability to anticipate, absorb, recover from, and adapt to emergencies while maintaining the continuity, accessibility, and quality of healthcare services. It is proved that ensuring systemic resilience requires a transition from fragmented managerial decisions to a comprehensive security-oriented approach that combines strategic restructuring, technological modernization, human resource development, standardization of clinical practices, risk management, and strengthening the institutional capacity of healthcare institutions.